2000
DOI: 10.1002/(sici)1099-1573(200002)14:1<60::aid-ptr597>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial activity of roots ofJatropha podagrica (Hook)

Abstract: Hexane, chloroform and methanol extracts of the rootwood and rootbarks of Jatropha podagrica were studied for their antimicrobial activity against 18 organisms. All the extracts exhibited some broad spectrum antibacterial activity, at a concentration of 20 mg/mL. The hexane extracts were generally more active than the chloroform and methanol extracts. The hexane extract of the yellow rootbark was the most active of all the extracts and its activity was comparable to that of gentamycin but better with regard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 6 publications
(5 reference statements)
2
21
0
Order By: Relevance
“…Various medicinal and pesticidal properties including antibacterial (pneumonia), antitumor and insect antifeedant have been attributed to this plant (Odebiyi, 1980). Phytochemicals in different parts of the plants includes flavonoids, steroids, alkaloids and diterpenoids have been isolated and characterized (Aiyelaagbe et al, 2007(Aiyelaagbe et al, , 1998; Das and Venkatail, 2006).…”
Section: Introductionsupporting
confidence: 93%
“…Various medicinal and pesticidal properties including antibacterial (pneumonia), antitumor and insect antifeedant have been attributed to this plant (Odebiyi, 1980). Phytochemicals in different parts of the plants includes flavonoids, steroids, alkaloids and diterpenoids have been isolated and characterized (Aiyelaagbe et al, 2007(Aiyelaagbe et al, , 1998; Das and Venkatail, 2006).…”
Section: Introductionsupporting
confidence: 93%
“…Different parts of J. podagrica are also used for antipyretic, diuretic, choleretic and purgative effects (Irvine 1961). Various medicinal and pesticidal properties, including antimicrobial, antitumour and insect antifeedant activities, have also been attributed to this plant (Aiyelaagbe et al 1998, Aiyelaagbe et al 2000, Bhaskarwar et al 2008, Sanni 1988.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment containing extracts from J. curcas pulp and seed showed significant differences in fungal development throughout the seven days after inoculation. Extracts of roots of Jatropha podagrica was reported to have moderate antifungal activity against Candida albicans (Aiyelaagbe et al, 1998). Our result is in agreement with the study of Ogbebor et al (2007) who reported that the J. curcas leaves extract inhibited the mycelium growth of C. gloeosporioides in 'Para' rubber tree.…”
Section: Resultsmentioning
confidence: 99%